2011
DOI: 10.1107/s090744491102779x
|View full text |Cite
|
Sign up to set email alerts
|

Acceleratingab initiophasing withde novomodels

Abstract: Ab initio phasing is one of the remaining challenges in protein crystallography. Recent progress in computational structure prediction has enabled the generation of de novo models with high enough accuracy to solve the phase problem ab initio. This `ab initio phasing with de novo models' method first generates a huge number of de novo models and then selects some lowest energy models to solve the phase problem using molecular replacement. The amount of CPU time required is huge even for small proteins and this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Out of the 10 targets tested, EdaFold succeeded in 5 targets as compared to 3 targets succeeded by Rosetta. The success in molecular replacement is not only judged by the TFZ score but also assessed by a verification procedure [6]. For , EdaFold and Rosetta manage to find a solution in molecular replacement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 10 targets tested, EdaFold succeeded in 5 targets as compared to 3 targets succeeded by Rosetta. The success in molecular replacement is not only judged by the TFZ score but also assessed by a verification procedure [6]. For , EdaFold and Rosetta manage to find a solution in molecular replacement.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the coarse-grained conformation sampling plays an important role in predicting highly accurate structure of proteins [5]. In addition, when coarse-grained models are predicted near native structure, switching the models to all-atom representation subsequently gives solutions in Molecular Replacement trials without extensive optimization [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational methods using coarse-grained models have already shown a great promise for a better description of protein structures, or their complexes, when combined with experimental data from NMR, 263,587−590 cryo-EM, 483,590−596 Xray 597,598 or SAXS. 589,599−601 In particular, recent combinations of the top performing multiscale structure prediction platforms, Rosetta and I-TASSER, with experimental measurements resulted in spectacular prediction results.…”
Section: Integrative Modelingmentioning
confidence: 99%
“…Energy-based methods using atomistic models have been used for fitting structures to low-resolution data, 2226 refining moderate to high-resolution X-ray data, 2729 providing low-to-moderate resolution models for use in crystal structure refinements, 30,31 folding some small proteins in MD simulations, 32 and docking macromolecules. 4 However, the success rate and accuracy of these and other applications of physics-based methods to macromolecular prediction problems remain substantially less than 100% (e.g.…”
Section: Summary and Discussionmentioning
confidence: 99%